Biokonversi Sampah Organik sebagai Wahana Edukasi dan Ketahanan Pangan: Bioconversion of Organic Waste as a Vehicle for Education and Food Security - Chabibah, Nur; Fitriyani, Fitriyani; Ersila, Wahyu; Nurtanti, Ina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
IMBS Miftakhul Ulum Pekajangan Pekalongan Islamic boarding school can produce more than fifteen buckets of organic waste, or equivalent to 30 kg per day. Waste management that is considered effective is using microorganisms, one of which is Black Soldier Flies (BSF). This community partnership program aims to encourage self-management of organic waste and improve knowledge and skills. The method used is lectures, Q&A discussions, training and demonstrations, waste processing practices, and vegetable and fish cultivation with an aquaponic system. The results of the activity showed an increase in knowledge (p-value = 0.000, CI = -3.699 to -2.336) and skills of managers and students of the boarding school in waste management with the organic waste bioconversion method based on BSF and vegetable and fish cultivation with an integrated aquaponic system solar panels. The training participants who came were 55 participants who were very enthusiastic in asking questions, and although only 22% of the target continued to be mentored. The conclusion is that organic waste management with a bioconversion system based on BSF, which is implemented sustainably, can result in increased knowledge, skills, and welfare for managers and students of the boarding school.